Antenatal Diagnosis of Fetal Genotype Determines if Maternal Hyperglycemia Due to a Glucokinase Mutation Requires Treatment - Chakera, Ali J. (American Diabetes Association, 2012)
OBJECTIVE: In women with hyperglycemia due to heterozygous glucokinase (GCK) mutations, the fetal genotype determines its growth. If the fetus inherits the mutation, birth weight is normal when maternal hyperglycemia is not treated, whereas intensive treatment may adversely reduce fetal growth. However, fetal genotype is not usually known antenatally, making treatment decisions difficult. HISTORY AND EXAMINATION: We report two women with gestational diabetes mellitus resulting from GCK mutations with hyperglycemia sufficient to merit treatment. INVESTIGATION: In both women, DNA from chorionic villus sampling, performed after high-risk aneuploidy screening, showed the fetus had inherited the GCK mutation. Therefore, maternal hyperglycemia was not treated. Both offspring had a normal birth weight and no peripartum complications. CONCLUSIONS: In pregnancies where the mother has hyperglycemia due to a GCK mutation, knowing the fetal GCK genotype guides the management of maternal hyperglycemia. Fetal genotyping should be performed when fetal DNA is available from invasive prenatal diagnostic testing.